Leadership and Ability of School Principals to Utilize an Asset-Based Approach as Learning Capital for Learning Based on Student Needs Based on School Potential (Literatur Review) - Soedjono, Soedjono; Prayito, Muhammad (Universitas PGRI Semarang, 2024)
Educational transformation is a phenomenon that always occurs in the dynamics of educational development. This research aims to explore school strategies for overcoming obstacles to educational transformation in schools. The methods used were the critical method, dialectical method, and scholastic method. This research was included in library research. The author tried to find data, and theories related to the issues raised in various literature or references that the author found and then compared them using the method mentioned above. The research results showed that the leadership style and use of an asset-based community approach were prospective alternatives for overcoming obstacles, especially financial limitations that exist in schools. The distributed and learning leadership style was an alternative leadership style that was a solution because this style could change the mindset of the entire school community in overcoming the obstacles that the school had been experiencing. A community-based approach had a great opportunity to overcome financial constraints through the formation and empowerment of educational communities within the school environment.